Early results of treatment for developmental dysplasia of the hip in children between the ages of one and four years - Karakurt, Lokman; Yilmaz, Erhan; Incesu, Mustafa; Belhan, Oktay; Serin, Erhan (My University, 2004)
OBJECTIVES: We evaluated the early results of treatment for developmental dysplasia of the hip in children between the ages of one and four years. METHODS: Twenty-four patients were retrospectively divided into two groups according to whether they were below or above two years of age at the time of the initial treatment. Group I consisted of 13 patients (20 hips; mean age 19.1 months; range 14 to 24 months); 11 patients (15 hips; mean age 32.6 months; range 26 to 50 months) comprised group II. Initially, patients in group I were treated with closed or open reduction (12 hips) and open reduction with femoral and/or pelvic osteotomies (8 hips). Group II patients underwent open reduction with femoral and/or pelvic osteotomies. Clinical results were evaluated according to the modified McKay criteria, and radiographic results to the Severin classification. The mean follow-up periods were 29.1 months (range 12 to 60 months) and 37.3 months (range 12 to 66 months), respectively. RESULTS: Subsequent operations were performed in nine hips in group I, and in two hips in group II (p<0.05). Avascular necrosis of the femoral head was noted in six hips (30%) in group I and in none of the hips in group II (p<0.05). Excellent or good radiographic results accounted for 85% and 86%, and clinical results for 90% and 100% in groups I and II, respectively. CONCLUSION: The need for pelvic and/or femoral osteotomies should be considered in conjunction with closed or open reduction in the treatment of developmental dysplasia of the hip in children between the ages of one and four years.
Yürüme çagindaki (1-4 yaş) gelişimsel kalça displazili olgularda erken dönem tedavi sonuçlarimiz.
Keywords: Child, Preschool; Female; Femur Head Necrosis; Hip Dislocation, Congenital; Humans; Infant; Male; Medical Records; Orthopedic Procedures; Osteotomy; Postoperative Complications; Reoperation; Retrospective Studies; Treatment Outcome; article; congenital hip dislocation; evaluation; female; femur head necrosis; human; infant; male; medical record; methodology; orthopedic surgery; osteotomy; pathology; postoperative complication; preschool child; radiography; reoperation; retrospective study; treatment outcome